Optimization of Personal Protective Equipment Distribution Costs to Health Centers with Stepping Stone Method - Nugroho, Arief Budi; Utami, Meinarini Catur; Putro, Suryo Santoso (Depart. of Information Systems, FST, UIN Syarif Hidayatullah Jakarta, 2023)
This study aims to apply the Stepping Stone transportation method to optimize transportation costs for sending personal protective equipment (PPE) to thirteen health centers in Pamekasan. The method used is the Stepping Stone transportation method because it can manage the distribution of several warehouses that provide products to be sent to places in need optimally, which was previously a problem due to the length of time for sending medicines and PPE to each health centre and shipping operational costs are increasing because the distance of each warehouse to each health centre in each sub-district is very influential for cost as well as time. Based on the results of transportation simulations with this method, the results of the distribution cost of PPE delivery to each health centre in Pamekasan were obtained with distribution to Pamekasan warehouses of 30,000 units, Pakong warehouses of 15,000 units, Tlanakan warehouses of 10,000 units, and Pasean warehouses of 19,500 units, with optimal costs of IDR 37,000,000. The contribution of this research can be used by the Pamekasan District Health Office as an alternative policy for distributing PPE to each health centre in Pamekasan at an optimal cost.